2004
DOI: 10.1001/archpsyc.61.7.705
|View full text |Cite
|
Sign up to set email alerts
|

Subtype-Specific Alterations of γ-Aminobutyric Acid and Glutamatein Patients With Major Depression

Abstract: The study replicates the findings of decreased GABA concentrations in the occipital cortex of subjects with MDD. It also demonstrates that there is a change in the ratio of excitatory-inhibitory neurotransmitter levels in the cortex of depressed subjects that may be related to altered brain function. Last, the combined data set suggests that magnetic resonance spectroscopy GABA measures may serve as a biological marker for a subtype of MDD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

32
477
7
19

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 733 publications
(535 citation statements)
references
References 70 publications
32
477
7
19
Order By: Relevance
“…Our preliminary results are in contrast to the Sanacora et al (2004) study which found below-normal glutamate and abovenormal GABA in the occipital lobes in melancholic unipolar patients. It is important to emphasize however, that the two studies differ in primary cohort (bipolar vs unipolar) and brain region of interest (anterior cingulated/medial prefrontal cortex vs occipital lobe).…”
Section: Discussioncontrasting
confidence: 99%
“…Our preliminary results are in contrast to the Sanacora et al (2004) study which found below-normal glutamate and abovenormal GABA in the occipital lobes in melancholic unipolar patients. It is important to emphasize however, that the two studies differ in primary cohort (bipolar vs unipolar) and brain region of interest (anterior cingulated/medial prefrontal cortex vs occipital lobe).…”
Section: Discussioncontrasting
confidence: 99%
“…The observations presented here, suggesting a deficit in GABAergic neurons in depression, are supported by recent clinical reports of reduced GABA levels in plasma and cerebrospinal fluid in mood disorder patients (Brambilla et al, 2003;Petty, 1995;Sanacora et al, 1999Sanacora et al, , 2004. A proton magnetic resonance spectroscopy study in live patients shows a highly significant 52% reduction in GABA levels in the occipital cortex of 14 medication-free depressed subjects (Sanacora et al, 1999).…”
Section: Discussionsupporting
confidence: 87%
“…No significant differences in the density of calbindin-immunoreactive (CB-IR) or parvalbumin-immunoreactive (PV-IR) GABAergic neurons were found between MDD and control groups in either cortical region. However, clinical evidence is emerging to suggest that MDD is associated with reduced levels of GABA in the plasma, cerebrospinal fluid, and neocortex (Petty, 1995;Sanacora et al, 1999Sanacora et al, , 2000Sanacora et al, , 2004. A proton magnetic resonance spectroscopy study revealed a large, 52% reduction in GABA levels in the occipital cortex of 14 medication-free depressed subjects as compared to 18 healthy control subjects (Sanacora et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…[43][44][45][46] The observation of a significant misexpression of molecules central to both GABAergic and glutamatergic neurotransmission in the cortical areas of individuals with major depression has been previously documented by several groups. 21,23,47 These studies follow on a body of clinical evidence showing that antidepressant medications may reduce glutamatergic activity while raising cortical GABA levels, which are seen to be reduced in major depression 48,49 and possibly also schizophrenia. 50,51 Since the two neurotransmitters are intimately connected by virtue of interconversion through glutamic acid decarboxylase in the synthesis of GABA from glutamate and the TCA cycle in the production of glutamate from GABA, it is difficult to disentangle the possible effects of these two molecules on the pathophysiology of depression and suicide.…”
Section: Discussionmentioning
confidence: 99%
“…In general, a growing body of evidence supports the involvement of GABA/ glutamate in cortical regions typified by BA46 in the DLPFC. [21][22][23] Two genes involved in the catabolism of polyamines (SAT and SMOX), significant in several regions, suggest the possible association of suicide and depression with defects in the polyamine stress response system. Reduced expression of SAT in depressed and nondepressed suicide groups was previously shown in motor cortex, superior frontal gyrus and orbital gyrus, 9 with correspondingly reduced levels of SAT protein.…”
Section: Discussionmentioning
confidence: 99%